Dead reckoning : memories of the 1971 bangladesh war - Bose, Sarmila ([S.l.] : Hurst, 2011)
This ground-breaking book chronicles the 1971 war in South Asia by reconstituting the memories of those on opposing sides of the conflict. 1971 was marked by a bitter civil war within Pakistan and war between India and Pakistan, backed respectively by the Soviet Union and the United States. It was fought over the territory of East Pakistan, which seceded to become Bangladesh. Through a detailed investigation of events on the ground, Sarmila Bose contextualises and humanises the war while analysing what the events reveal about the nature of the conflict itself. The story of 1971 has so far been dominated by the narrative of the victorious side. All parties to the war are still largely imprisoned by wartime partisan mythologies. Bose reconstructs events via interviews conducted in Bangladesh and Pakistan, published and unpublished reminiscences in Bengali and English of participants on all sides, official documents, foreign media reports and other sources. Her book challenges assumptions about the nature of the conflict, and exposes the ways in which the 1971 war is still playing out in the region.
Keywords: Bangladesh; Collective memory; Interviews; Revolution (Bangladesh : 1971); Social aspects; War and society; War victims